A Study About The Power Flow In Brushless Doubly Fed Asynchronous Generators For Wind Power Systems - Voltolini, Hélio; Carlson, Renato; Rüncos, Fredemar (Eletrônica de Potência, 2006)
This paper presents dynamic modeling and simulation of Brushless Doubly Fed Induction Generator (BDFIG) as an alternative for variable speed wind power applications. The mathematic models of active and reactive power for BDFIG have been developed. The power control systems of a 75 kVA generator and wind turbine were simulated in Matlab/Simulink/SymPower Systems. The generator’s control system is based on vector control principles which enable to decouple active and reactive power control. The power flow in the two stator windings and in the grid is analyzed in two different power factor correction schemes. The results presented show that the rating of the two converters used in this system can be calculated considering that both converters are compensating reactive power. It allows a reduction of the kVA rating of the auxiliary-side converter.